An exploratory study about the evaluation of children's books market in Turkey - Bilgin, Zeynep. (Thesis (M.A.)- Bogazici University. Institute for Graduate Studies in Social Sciences, 1985., 1985)
In this thesis, an evaluation of the children's books market in Turkey has been studied thoroughly. For this purpose, the importance of developing reading habit in the childhood was the starting point. By analysing the children's books market, el!lphasis was put on how an ideal children's book has to be written, which characteristics it has to possess and to what extent the children's books in the market meet these requirements. The overall evaluation on the children's books market also displays the problems people in the field are faced with. The study includes literature review, experience survey and field survey. Literature review is based on the analysis of the studies from U.S.A., Austria and Tl\rkey. For the experience survey, knowledgable people in the area of children literature and children's books market such as authors, illustrators, publishers, sales personnel and parents have been interviewed. For the field survey, after having conducted two pilot studies -one in Germany the second in Turkey-, a questionnaire was given to children in the third grade of a primary school in Istanbul. Data was analysed and findings displayed with the implications for the marketers and researchers. The findings of the research show that children literature in Turkey is still at the infancy stage. There are very few Turkish authors who really care and write for children. A high percentage of the books in the market are translations from literature of other countries. Most important points related to children's books seem to be based on content and form of the book. The content includes theme, diction, narration and translation qualities. The form includes letter size, illustrations, print quality and general appearance of the book. These factors have been analysed for three groups of books: Picture books, Novel books and Informative books. Although in general the required characteristics for an ideal content or form are well known to all people contacted, the books in the market seem not exactly meeting the necessary standards and especially for from and appearance the specifications are not at satisfactory level. The study also shows that there is no effective organization or any attempt to ensure a well planned introduction for the new publications and to make any critics or evaluations about the children's books in the market.
Keywords: Children's literature -- Publishing -- Turkey.; Children's literature -- Marketing.; Children's literature -- Turkey -- Study and teaching.